Planck 2015 results XXII. A map of the thermal Sunyaev-Zeldovich effect - Aghanim, N.; Arnaud, M.; Ashdown, M.; Aumont, J.; Baccigalupi, C.; Banday, A. J.; Barreiro, R. B.; Bartlett, J. G.; Bartolo, N.; Battaner, E.; Battye, R.; Benabed, K.; et al. (Edp Sciences S A, 2016)
We have constructed all-sky Compton parameters maps, y-maps, of the thermal Sunyaev-Zeldovich (tSZ) effect by applying specifically tailored component separation algorithms to the 30 to 857 GHz frequency channel maps from the Planck satellite. These reconstructed y-maps are delivered as part of the Planck 2015 release. The y-maps are characterized in terms of noise properties and residual foreground contamination, mainly thermal dust emission at large angular scales, and cosmic infrared background and extragalactic point sources at small angular scales. Specific masks are defined to minimize foreground residuals and systematics. Using these masks, we compute the y-map angular power spectrum and higher order statistics. From these we conclude that the y-map is dominated by tSZ signal in the multipole range, 20 < l < 600. We compare the measured tSZ power spectrum and higher order statistics to various physically motivated models and discuss the implications of our results in terms of cluster physics and cosmology.
Keywords: large-scale structure of Universe; cosmology: observations